2016
DOI: 10.3390/su8010098
|View full text |Cite
|
Sign up to set email alerts
|

Possible Futures towards a Wood-Based Bioeconomy: A Scenario Analysis for Germany

Abstract: Driven by the growing awareness of the finite nature of fossil raw materials and the need for sustainable pathways of industrial production, the bio-based economy is expected to expand worldwide. Policy strategies such as the European Union Bioeconomy Strategy and national bioeconomy strategies foster this process. Besides the advantages promised by a transition towards a sustainable bioeconomy, these processes have to cope with significant uncertainties as many influencing factors play a role, such as climate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 46 publications
1
59
0
3
Order By: Relevance
“…In this regard, although it was stressed during the focus group exercise and expert interviews that consumers still have very little understanding of "bio-based" as a concept [62], they are at the same time aware of the higher pricing of bio-based products in comparison with more traditional products. In line with the literature (see [61,63]), we found that the willingness to pay represents a key factor. More specifically, the health and safety of consumers appears to be the factor that most influences the consumer's willingness to pay.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In this regard, although it was stressed during the focus group exercise and expert interviews that consumers still have very little understanding of "bio-based" as a concept [62], they are at the same time aware of the higher pricing of bio-based products in comparison with more traditional products. In line with the literature (see [61,63]), we found that the willingness to pay represents a key factor. More specifically, the health and safety of consumers appears to be the factor that most influences the consumer's willingness to pay.…”
Section: Discussionsupporting
confidence: 76%
“…To this end, an SLCA therefore becomes crucial to compare "options, especially when complex supply chains are involved" [59]. In fact, for a market uptake of bio-based products, certain necessary conditions must be achieved, not only in terms of the implementation of appropriate policies (see, e.g., [17,60]) but also on the conditions that relate directly to consumer acceptability (see [61]). …”
Section: Discussionmentioning
confidence: 99%
“…Appelrath et al 2016). A good example of bioeconomy-related qualitative scenarios is OECD (2009) (Kovacs 2015;Hagemann et al 2016).…”
Section: Explorative Scenariosmentioning
confidence: 99%
“…solvent or supercritical water extraction, hydrolysis of the biomass, resulting in valuable bio-based substances from technological batches from biofuel or food production technologies (Naik et al 2010;Nattrass et al 2016;Snyder 2016). This is supported by the European Bioeconomy Panel and the SCAR Strategic Working Group of the European Commission (EC 2014), and is best exemplified by the cascade use of biomass in the wood industry (Scarlat et al 2015;Hagemann et al 2016). Chemicals/plastics and pharmaceuticals so far represent only 10% of the annual turnover of the bio-based sector (Piotrowski et al 2016), yet this may be considered the most promising segment within the sector, as bio-based chemicals are being produced in closed system technologies, representing the lowest hazard to the environment.…”
Section: Bio-based Productsmentioning
confidence: 99%